Adaptation indicator to climate change and farm sizes in agriculture: A reflection of farming culture and history - Husniddin Sharofiddinov; Moinul Islam; Koji Kotani (Ecological Indicators)
Climate change is a global concern, having a negative impact on agriculture, for food security and sustainability. Farmers’ adaptations are known to be key drivers for the resolutions. However, little is established about relationships between farmers’ characteristics and adaptation responses to climate change under irrigated agriculture. We investigate how farm sizes influence the adaptations in consideration to irrigation-related, cognitive and socioecological factors reflecting farming culture and history, hypothesizing that large-size farms adapt to climate change as compared to small-size ones in Tajikistan, where collective farming, “Kolkhoz and Sovkhoz,” had been practiced. The data were collected through a questionnaire survey with 800 farmers on their adaptations, farm sizes, climatic perceptions, irrigation water availability and other factors. We conduct statistical analyses utilizing the indicator to characterize farmers’ adaptation responses. The results indicate an importance of farm sizes on adaptations, demonstrating that small-size farms adapt less than large-size farms, but increases their adaptations when they have good climatic perceptions and irrigation water availability. Overall, this research confirms an advantage of large-size farms for adaptations based on Tajikistan farming culture and history. Thus, the ongoing land-fragmentation policy should be reconsidered for possible losses in adaptations, as it has been drastically increasing the number of small-size farms. Otherwise, it is essential to support the small-size farms for acquiring good perceptions and enough water.